Case Presentation: Re-revision Quad Tendon Repair and Vastus Advancement - Amar S. Vadhera BS; Safa Gursoy MD, PhD; Lakshman Sivasundaram MD; Jonathan S. Lee BA; Harsh Singh BA; Sean Bunachita BA; Jorge Chahla MD, PhD (SAGE Publishing, 2023)
Background: The quadriceps tendon is crucial in allowing knee extension, attaching distally to the patella. While ruptures of the tendon are rare, retear can lead to muscle atrophy and complex tendon deficits with retraction which may make revision repairs difficult to perform. To avoid re-rupture, the repair is commonly augmented with an allograft or autograft, theoretically strengthening the repair. Indications: Patients are indicated for surgery when presenting with a chronic, symptomatic quadriceps rupture verified on provocative testing and advanced imaging. Technique Description: Adhesions and fibrotic tissues around the vastus muscles and tendon are released. Sutures and anchor materials from the previous reconstruction are removed. Fibrotic tissues at the distal end of the retracted quad tendon are removed. The tendon is then loosened from the proximal aspect with the applied traction through the suspension suture placed distal to the tendon. The gap is measured and a V-Y quadricepsplasty was performed at twice the length of the measured gap. In the proximal aspect of the tendon, the limbs of the V-plasty are left incomplete. Next, traction is applied to allow for a tightening exertion to the patella. The proximal Y limb is sutured together in a side-to-side fashion to allow for tendon distalization while retaining the distal traction of the patellar tendon. The medial and lateral limbs were then closed with a suture, completing the tendon advancement. Fibrotic tissues around the superior pole of the patella are removed to prepare for tendon reattachment. Two anchors on the medial and lateral sides are placed, and the suture threads from both anchors are tied in a Krackow configuration. The medial and lateral-sided suture knots are then tied together over the tendon and covered again with the Achilles allograft, completing the repair. Results: Outcomes of revision quadriceps repair have been promising, with good to excellent functional outcomes, successful return to activities, and objective outcomes. Discussion/Conclusion: Although initial studies report favorable outcomes following current repair techniques, there is a lack of quality literature on outcomes following primary or revision quadriceps repair. Future studies are necessary to determine the reliability, efficacy, and clinical outcomes following this procedure. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.